PENGARUH WAKTU DEKOMPOSISI LUMPUR AKTIF BASAH DARI UNIT PENGOLAHAN LIMBAH PABRIK CRUMB RUBBER PADA PROSES PEMBUATAN PUPUK ORGANIK - Nurhayati, Chasri; Susilawati, Nesi (Jurnal Dinamika Penelitian Industri, 2018)
Actived sludge from waste water treatment Â of crumb rubber industry of PT Hoktong Plaju in PalembangÂ  still contains nutrients and other useful elements for living plants. Actived sludge containts the composition of 70%-90% of organic compound and 10 % of inorganic. The purpose of this research in to find out the composition of nutrients from various time composting organic fertilizer made from wet active mud of rubber crumb factory waste. The design for this experiment was Complete Randomized Design with 3 different time variables for composting. Variable 1 (7 days of composting time), Variable 2 (9 days of composting time) and Variable 3 (15 days of composting time) all of the treatments were repeated three times. Organic fertilizer that have been composted are then subjected to quality testing in accordance with SNI (Indonesian National Standard) for organic fertilizer from domestic waste for organic C parameters, C / N, Ikutan, Nitrogen, P2O5, K2O, Metals and Micro nutrients. From this research is concluded that wet active mud from crumb rubber factory waste processing unit can be used as raw material of compost fertilizer because it contains organic C, C / N, Ikutan, Nitrogen, P2O5, K2O, Metals and Micro nutrients according to SNI organic fertilizer from domestic waste and the Ministry of Agriculture Regulation number 79/SR/140/10/2011 about Minimum Technical Requirements of Organic Fertilizer from Industrial Wastewater Treatment Plant. From the treatment performed, Variable 3 with the composting time of 15 days is the best treatment to raise the level of nutrients in wet mud. In the case where the nutrients levels are not fulfilled, the addition of organic ingredients that contains Kalium elements can be done in the composting process.